ANALISIS GAGALNYA KOPERASI DI KOTA BATAM - Tiurniari Purba; Heryenzus Heryenzus (LPPM Universitas Putera Batam, 2019)
This study aims to analyze the problems in cooperative institutions located in the Batam City, especially issues concerning the resources of civil servants of the cooperative service, coaching programs and assistance of the cooperative service, infrastructure facilities from the cooperative office, communication and coordination between cooperatives with stakeholders. The population in this study is cooperative in Batam City area, especially in nine districts with 844 cooperatives. This research uses qualitative research with case study approach because the problem in this research happened directly in real life. Case study data can be obtained not only from the cases studied, but also can be obtained from all parties who know and know the case well. In other words, the data in the case study can be obtained from various sources but limited in the case to be investigated. The results showed that the Office of PMP KUKM Batam City to enliven the cooperatives of 922 cooperatives and 526 of them have died and some are dispersed, never know despair. Coaching and mentoring programs, training human resources of cooperative, fixing infrastructure, and connecting communications and coordination between cooperatives and stakeholders, never enough even there is always the latest effort like cooperative consultation clinic. The counseling consultative clinic is directed or follows the roadmap or milestone in the short, medium and long term.